Implementation of Web-based Document Signing and Data Validation System - Febian Bahy, Raihan; Faris Ruriawan, Muhammad; Purwanto, Yudha (Green Publisher Indonesia, 2022)
The physical form of documents has changed a lot, previously documents can only be used if they have been printed, now documents can also be used in digital form only. However, along with the change in the physical form of the document, it also does not close the crimes that occur, such as falsifying documents, especially in the ratification or signing section. The digital document validation process combines digital document signing techniques with cryptographic algorithms, the cryptographic algorithm used is the Base64 algorithm. By combining the Base64 cryptographic algorithm and MD5 hashing, it is hoped that a method will be created to validate secure digital documents while maintaining the C.I.A (Confidentiality, Integrity, and Availability) aspects in the world of cryptography. Henceforth, the result of this final project is the creation of a digital platform or website that functions to validate digital documents by combining Base64 cryptographic techniques and MD5 hashing algorithms as data security protection. This document validation application has features such as user management, input, edit, delete, and the main features of document validation with a success rate of 100% from black box testing and white box testing. As for the performance test, the fastest time is when the system deletes data, with an average time of 0.14s, while the longest time is when the system updates data, with an average time of 0.70s.